Air microbial contamination in dental clinics: comparison between active and passive methods - Veronesi, Licia; Colucci, Maria Eugenia; Napoli, Christian; Castiglia, Paolo; Liguori, Giorgio; Torre, Ida; Righi, Elena; Farruggia, Patrizia; Tesauro, Marina; Montagna, Maria Teresa; Gallè, Francesca; Masia, Maria Dolores; et al. (Acta Biomedica Atenei Parmensis, 2020)
The aim of this study was to evaluate the correlation between the microbial air contamination values obtained by active sampling (colony-forming units per cubic metre, CFU/m3) and by passive sampling (Index of microbial air contamination, IMA) and to calculate the corresponding equations. Air sampling was performed in ten dental clinics (DC), before (T0), during (T1) and after (T2) the clinical activity, for five consecutive days, once a month for a period of three months, for a total of 450 air samplings. The correlation was evaluated using the Spearman test, and a p value below 0.05 was considered statistically significant. A statistically significant correlation was found considering both the results obtained from the total observations and from the single sampling times, T0, T1 and T2. Different correlation patterns were observed stratifying by DC. Both methods were able to evaluate the microbial air quality and highlight critical situations; therefore, both can be used with this aim. However, in particular during the activity, passive sampling resulted more sensitive, and for its simplicity, economy and standardization by IMA, as suggested by several authors, can be suggested for routine monitoring.